Using trig identities, prove the equation shown below. sec(x) – sin(x)tan(x) = cosx Hint: Work on the left side

Question

Using trig identities, prove the equation shown below.

sec(x) – sin(x)tan(x) = cosx

Hint: Work on the left side of the equation and do not manipulate the right side of the equation.

in progress 0
Adeline 2 weeks 2021-09-26T20:33:56+00:00 1 Answer 0

Answers ( )

    0
    2021-09-26T20:35:19+00:00

    Answer:

    Step-by-step explanation:

    Prove that

    sec(x) – sin(x)tan(x)=cosx

    sec(x)=1/cos(x) tan(x)=sin(x)/cos(x)

    1/cos(x) – sin(x) x sin(x)/cos(x)

    (1-sin(x) x sin(x))/cos(x)

    (1-sin^2(x))/cos(x) 1-sin^2(x)=cos^2(x)

    Cos^2(x)/cos(x)

    (Cos(x) x cos(x))/cos(x)

    cos(x) proved

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )